BIOMOLECULAR ACTIVITY OF CRYPTOCOCCUS DURING CRYPTOCOCCOSIS: FOCUS ON REVIEW OF MOLECULAR INTERACTION CRYPTOCOCCUS WITH HUMAN IMMUNE SYSTEM AND BLOOD-BRAIN BARRIER - Julian, Julian; Adawiyah, Robiatul; Wahdini, Sri (African Journal of Infectious Diseases (AJID), 2023)
Global mycosis is still a problem. One of these is the cryptococcal disease. A systemic mycosis brought on by Cryptococcus is called cryptococcosis. Host immunological conditions influence infection with Cryptococcosis. When environmental spores are inhaled by the host, the spores get to the lungs, an infection is created. Alveolar macrophages and other immune cells recognize Cryptococcus in the lung. The initial line of defense against pathogens in the phagolysosome is provided by alveolar macrophages found in the lungs. When the immune system is weak, Cryptococcus uses the evasion system as a molecular interaction with the immune system and persists in the lungs without causing any symptoms such as Factor Transcription, Cell masking, N-glycan structure, Extracellular molecule, and Antioxidant system. The evasion mechanism protects and makes Cryptococcus disseminate throughout the other organs, especially CNS. If Cryptococcus escapes against the host immune system, it will disseminate to other organs, especially Cerebrospinal System by Three mechanisms. There are Trojan Horse, Paracellular, and Transcellular interactions with Blood-Brain Barrier. Disease severity is determined by the Interaction between the host’s immune system and the fungus